The multiple myeloma risk allele at 5q15 lowers ELL2 expression and increases ribosomal gene expression - Ali, Mina; Ajore, Ram; Wihlborg, Anna-Karin; Niroula, Abhishek; Swaminathan, Bhairavi; Johnsson, Ellinor; Stephens, Owen W.; Morgan, Gareth; Meissner, Tobias; Turesson, Ingemar; Goldschmidt, Hartmut; Mellqvist, Ulf-Henrik; et al. (Nature Communications, 2018)
Recently, we identified ELL2 as a susceptibility gene for multiple myeloma (MM). To understand its mechanism of action, we performed expression quantitative trait locus analysis in CD138+ plasma cells from 1630 MM patients from four populations. We show that the MM risk allele lowers ELL2 expression in these cells (Pcombined = 2.5 × 10−27; βcombined = −0.24 SD), but not in peripheral blood or other tissues. Consistent with this, several variants representing the MM risk allele map to regulatory genomic regions, and three yield reduced transcriptional activity in plasmocytoma cell lines. One of these (rs3777189-C) co-locates with the best-supported lead variants for ELL2 expression and MM risk, and reduces binding of MAFF/G/K family transcription factors. Moreover, further analysis reveals that the MM risk allele associates with upregulation of gene sets related to ribosome biogenesis, and knockout/knockdown and rescue experiments in plasmocytoma cell lines support a cause-effect relationship. Our results provide mechanistic insight into MM predisposition.
Gesehen am 01.07.2020